The Effect of Viral Marketing on the Purchasing Decisions of Women's Park Customers in Misurata - Al-Bayoudy, Fatima; Endara, Youssef (Sharwes Scientific Journal, 2025)
The study aimed to analyze the impact of viral marketing on customer purchase decisions at women's parks in Misrata. The study focused on four main dimensions: viral advertising campaigns, opinion leaders (influencers), electronic publishing media, and financial incentives. To achieve the research objectives, a descriptive analytical approach was used. The primary research tool was a questionnaire based on the Curtis five-point scale. A simple random sample of 384 randomly selected customers was distributed. SmartPLS software was used to analyze the structural model and test hypotheses .Among the most important findings of the study is that there is a statistically significant positive impact on electronic publishing media and opinion leaders (influencers), as they played a significant role in guiding purchase decisions. The results, however, showed a negative and weak impact of viral advertising campaigns and financial incentives on purchase decisions. The four dimensions explained 25.9% of the change in purchase decisions . The study recommended focusing on social media as a primary tool in viral marketing and improving the quality of advertising content to make it more attractive. And interactive. Re-evaluating financial incentive strategies, as they were not effective in this study, will improve their digital marketing strategies .